2023
DOI: 10.3390/plants12102043
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Chestnut Extract and Its Components on Antibacterial Activity against Staphylococcus aureus

Abstract: Increasing antimicrobial resistance has caused a great interest in natural products as alternatives or potentiators of antibiotics. The objective of this study was to isolate individual tannins from crude chestnut extract as well as to determine the influence of both crude extracts (tannic acid extract, chestnut extract) and individual pure tannins (gallic acid, vescalin, vescalagin, castalin, castalagin) on the growth of Gram-positive Staphylococcus aureus bacteria. Their antibacterial activity was monitored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…These findings are supported by previous studies that antibacterial activities are dose dependent. Stumpf et al 36 reported the growth inhibitory concentrations of the tannins against Staphylococcus aureus and found that these values increase with increasing concentration in the growth medium. These findings are also supported by a study conducted by Kolenc et al 37 that antibacterial activity of plants extracts against S. aureus and L. acidophilus was also dose dependent.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are supported by previous studies that antibacterial activities are dose dependent. Stumpf et al 36 reported the growth inhibitory concentrations of the tannins against Staphylococcus aureus and found that these values increase with increasing concentration in the growth medium. These findings are also supported by a study conducted by Kolenc et al 37 that antibacterial activity of plants extracts against S. aureus and L. acidophilus was also dose dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Extracts and phytocompounds from Humulus lupulus showed significant activity against S. aureus compared to their response against Lactobacillus acidophilus [35]. Similarly, the antimicrobial activity of the tannins of the chestnut extract was noted, while this response was pronounced in the case of E. coli, and hence reflected the availability of potential alternative to antimicrobials [36]. The In silico inverse molecular docking procedures have been used previously to measure antimicrobial activity of rosemary extracts [37].…”
Section: Discussionmentioning
confidence: 99%
“…Punicalagin, in particular, demonstrates the potential to suppress the resistance of S. aureus to the antibiotic oxacillin, indicating synergistic action with the antibiotic [ 238 ]. Additionally, vescalagin, castalagin, vescalin, and castalin, representatives of ellagitannins obtained from crude chestnut extract, demonstrate better antibacterial activity against E. coli compared to S. aureus , suggesting a varying action of tannins based on their structural differences [ 247 ]. Procyanidin and prodelphinidin, as proanthocyanidins, demonstrate good antibacterial activity, particularly against gram-positive bacteria associated with skin diseases, such as Staphylococcus epidermidis , Salmonella enterica ser.…”
Section: Biological Activity Of Plant Tanninsmentioning
confidence: 99%